2010
DOI: 10.4236/ns.2010.26078
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties for N,N’-bis (lnaphyhly)N,N’-diphenyl-1,1’-biphenyl-4,4’-diamine and tris (8-hydroxyquinolinato) aluminum in organic light emitting devices

Abstract: The optical properties of N,N'-bis (Inaphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (NPB) and tris (8-hydroxyquinolinato) aluminum (Alq 3) organic materials used as hole transport and electron transport layers in organic light-emitting devices (OLED) have been investigated. The NPB and Alq 3 layers were prepared using thermal evaporation method. The results show that the energy band gap of Alq 3 is thickness independence while the energy band gap of NPB decreases with the increasing of sample thickness. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Currently, there is great research has been demonstrated in the study of Organic Light-Emitting Devices (OLEDs) for full-color display application (Lim et al, 2010a;2010b). OLEDs have an organic EL medium consisting of extremely thin layers sandwiched by two electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is great research has been demonstrated in the study of Organic Light-Emitting Devices (OLEDs) for full-color display application (Lim et al, 2010a;2010b). OLEDs have an organic EL medium consisting of extremely thin layers sandwiched by two electrodes.…”
Section: Introductionmentioning
confidence: 99%